Development of fiber cement boards using kapok fiber and human hair as an alternative cellulose fiber - Magarso, A. J. Christian D. (2023)
The evolving construction industry emphasizes on discovering new components that may be used effectively for production to create building materials that are economical and sustainable. For the same reason, combining natural fibers with engineered materials has emerged as the newest trend in building construction. In this research, the adaptability of natural fibers is tested to generate an alternative building material specific to fiber cement boards. Kapok fiber and human hair fiber were the alternative cellulose fiber source that were tested in this study. The produced kapok-hair fiber cement boards underwent physical and mechanical tests that determined the idealproportions, mixing, and curing techniques. The created material was also compared to commercially available fiber cement boards to assess its potential.Based on the gathered data, it can be concluded that the KHFCB or Kapok-Hair Fiber Cement Boards can be a viable alternative for commercially available fiber cement boards. It conformed to the physical and mechanical standards for a Type B fiber cement flat sheet making it best for internal drywall applications where it will not be subjected to direct sun and rain. It only failed to be a good thermal insulator, so a supplementary insulating material is needed for optimal thermal insulation.